Routine Administration of a Multispecies Probiotic Containing Bifidobacterium and Lactobacillus to Very Low Birth Weight Infants Had No Significant Impact on the Incidence of Necrotizing Enterocolitis - Brian A. Juber; Brian A. Juber; Timothy J. Boly; Graeme J. Pitcher; Steven J. McElroy (Frontiers Media S.A., 2021)
Background: Necrotizing enterocolitis (NEC) is the leading cause of gastrointestinal morbidity in preterm infants, and prevention and treatment strategies have remained largely unchanged over the past several decades. As understanding of the microbiome has increased, probiotics have been hypothesized as a possible strategy for decreasing rates of NEC, and several studies have noted significant decreases in rates of NEC after initiation of probiotics in preterm infants. However, a recent AAP report cited caution on the use of probiotic use in part because studies of probiotic use in ELBW infants are lacking. As our unit began routine use of probiotics for all infants <33 weeks in 2015 and we are a leading institution for intact survival of ELBW infants, we attempted to answer if probiotic use can impact the rate of NEC in VLBW and ELBW infants.Methods: We conducted a single-center retrospective chart review of infants with modified Bell's stage ≥2a NEC for the 4 years prior to and 5 years after initiation of a protocol involving routine supplementation of a multispecies probiotic to premature infants at the University of Iowa, Stead Family Children's Hospital. The primary outcome measures were rates of modified Bell's stage ≥2a NEC and all-cause pre-discharge mortality at our institution before and after initiation of routine probiotic supplementation in 2015.Results: In our institution, neither the rates of modified Bell's stage ≥2a NEC, nor the rates of all-cause mortality were significantly altered in very low birth weight (VLBW) infants by the initiation of routine probiotic use (NEC rates pre-probiotic 2.1% vs. post-probiotic 1.5%; all-cause mortality rates pre-probiotic 8.4% vs. post-probiotic 7.4%). Characteristics of our two cohorts were overall similar except for a significantly lower 5-minute APGAR score in infants in the post-probiotic epoch (pre-probiotic 8 vs. post-probiotic 6 p = 0.0316), and significantly more infants in the post-probiotic epoch received probiotics (pre-probiotics 0% vs. post-probiotics 65%; p < 0.0001). Similarly, probiotic use had no impact on the incidence of NEC when we restricted our data to only extremely low birth weight (ELBW) infants (pre-probiotics 1.6% vs post-probiotics 4.1%). When we restricted our analysis to only inborn infants, probiotics still had no impact on NEC rates in VLBW infants (1.5% pre- and 1.1% post-probiotic, p = 0.61) or ELBW infants (2% pre- and 2.1% post-probiotic, p = 0.99)Conclusions: Contrary to other studies, we found no significant difference in rates of modified Bell's stage ≥2a NEC or all-cause pre-discharge mortality in VLBW infants following routine administration of a multispecies probiotic supplement.